Common malaria Mosquito Anopheles quadrimaculatus Say (Insecta: Diptera: Culicidea) - Leslie M. Rios; C. Roxanne Rutledge-Connelly (EDIS)
EENY-491, a 6-page illustrated fact sheet by Leslie M. Rios and C. Roxanne Connelly, describes this historically most important vector of malaria in the eastern United States — synonymy, distribution, description, life cycle, medical significance, surveillance, and management. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009.